Manajemen Konflik Pertanahan: Studi Kasus Sengketa Tanah Pasar Umum Gianyar Oleh Bendesa Adat Gianyar Dengan Pemerintah Kabupaten Gianyar Tahun 2019-2021 - Pramesti, Desak Ayu Mas Dinda; Erviantono, Tedi; Noak, Piers Andreas (Jurnal Nawala Politika, 2022)
This study aims to determine the pattern of resolving conflicts over land disputes in the Gianyar Public Market between bendesa adat Gianyar and the Gianyar Regency Government until 2021. Conflict Management Theory in the form of mediation from Jacob Bercovith which was used as an analysis knife to dissect the factors of mediation failure between bendesa Adat Gianyar and the Gianyar district government. Using qualitative methods through interviews, the results of the study were obtained as follows: First, the factors of failure in the mediation process. Second, look at the relationship between the Gianyar district government and the Gianyar Traditional Village. Third, look at how the Gianyar district government takes a decision related to indigenous villages. Fifth, look at how indigenous villages fight for ancestral heritage and see how the Gianyar district government, namely the Regent who has the highest power in Gianyar district, takes a stand with the conflict over the Gianyar Public Market land dispute.